2007
DOI: 10.1007/s00464-007-9251-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic perforations: a review of 30,366 patients

Abstract: Background: Although the incidence of perforation after endoscopic procedures of the colon is low, the rising number of procedures could pose relevant health problems. Recognizing risk factors and optimizing treatment may reduce perforation incidence and the probability of (severe) complications. This study aimed to determine perforation frequency and the management of endoscopic colonoscopic perforation. Methods: A retrospective review of patient records was performed for all patients with iatrogenic colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
2
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(228 citation statements)
references
References 24 publications
10
189
2
14
Order By: Relevance
“…In a retrospective study on more than thirty thousand patients, it was found to be only 0.1% [2]. Perforations may be pneumatic due to excessive distension of the intestinal wall from high-pressure insufflations or mechanic from the pressure exerted by the gastroenterologist [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study on more than thirty thousand patients, it was found to be only 0.1% [2]. Perforations may be pneumatic due to excessive distension of the intestinal wall from high-pressure insufflations or mechanic from the pressure exerted by the gastroenterologist [3].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal perforation following colonoscopy represents a rare complication [2]. In a retrospective study on more than thirty thousand patients, it was found to be only 0.1% [2].…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, we assumed a small risk of complications such as bowel perforations after colonography and colonoscopy. 37,38 The costs of these complications are also taken into account. Since there are no data on costs of complications after colonography, we assumed these to be equal to the costs of complications after colonoscopy.…”
Section: Screening Strategiesmentioning
confidence: 99%
“…Traditionally, surgery is the only rescue treatment for this iatrogenic perforation. [1][2][3] Recently, with the application of many endoscopic gadgets such as stent, band, endoclip, an endoscopic closure could be employed as the primary treatment for perforation 4 and this in turn may result to the lower rate of morbidity than the previous surgical approach. 5 …”
Section: Introductionmentioning
confidence: 99%